Quality of life and depression in patients with primary open angle glaucoma using Malay version of glaucoma quality of life 36 and Malay version geriatric depression scale 14 questionnaires - Tharmathurai, Sangeetha (2016)
INTRODUCTION Glaucoma is a chronic disease requiring life long treatment. Quality of life (QoL) is often under emphasized during the course of glaucoma management. Understanding the quality of life and detection of early depression at different severity stage of POAG not only helps in coping with the disease but also in customization of the management. There is still a wide gap in understanding the QoL and depression in elderly with POAG in Malaysia. OBJECTIVE To evaluate quality of life and depression in patients with primary open angle glaucoma using the Malay version of the Glaucoma Quality of Life- 36 (Glau-QoL 36) and malay version Geriatric Depression Scale 14 (mGDS 14) questionnaires. This study also aims to compare the QoL and depression with severity of POAG. The potential correlation between QoL and depression was also studied. METHODS A cross sectional study was conducted in Hospital Universiti Sains Malaysia, Kelantan and Hospital Selayang, Selangor between July 2014 and February 2016. POAG patients who were ≥ 60 years old at the time of recruitment had mLOCS II grade 1 or less, underwent cataract or trabeculectomy surgery at least 3 months prior and were on medical or combined medical and surgical treatment. Severity of POAG was based on modified Advanced Glaucoma Intervention Study (AGIS) based on two reliable reproducible Humphrey visual field SITA program 24-2 analysis. Face to face interview was conducted using validated Bahasa Malaysia version of GlauQol 36 and mGDS 14 questionnaires. RESULTS A total of 360 patients were recruited. Majority of recruited patients were between ages 60-67 (38.3%). Overall 64 (17.8%) have mild POAG, 93 (25.8%) have moderate POAG, 115 (31.9%) have severe POAG and 88 (24.4%) have end stage POAG. Majority of the recruited patients were not working (88.9%) and live with their families (68.1%). There was significant association between GlauQoL 36 score among POAG patients according to severity and domains: daily living, driving, physiological well being, self image, anxiety, burden of treatment and confidence in healthcare. Increased severity of POAG was associated with dectresed quality of life in all GlauQoL 36 domains except confidence in healthcare. There were more depressive patients as severity of POAG increased. There was poor correlation between quality of life and depression among POAG patients ( r <0.25). CONCLUSION Bahasa Malaysia version of GlauQoL 36 and mGDS 14 is a useful tool to assess QoL and depression of POAG patients in Malaysia. GlauQoL 36 scores increased as the severity of glaucoma increases suggestive of poorer quality of life. The mGDS 14 score also increases as the severity of glaucoma increases. However, there was poor correlation between QoL and depression based on the mGDS 14 and GlauQoL 36 questionnaire.